CHEBYSHEV SUBALGEBRAS OF JB-ALGEBRAS (Journal of Sciences, Islamic Republic of Iran)
In this note, we characterize Chebyshev subalgebras of unital JB-algebras. We exhibit that if B is Chebyshev subalgebra of a unital JB-algebra A, then either B is a trivial subalgebra of A or A= H R .l, where H is a Hilbert space